ZimFlores: a model to advice co-management of the Mafungautsi forest in zimbabwe - Prabhu, Ravi; Haggith, M.; Mudavanhu, H.; Muetzelfeldt, R.; Standa-Gunda, W.; Vanclay, J.K. (2003)
Zimbabwe Forest Land Oriented Resource Envisioning System (ZimFlores) version 4 is the outcome of a participatory modelling process and seeks to provide a shared factual basis for exploring land-use options for the communal lands surrounding the Mafungautsi forest. The ZimFlores experience underscores the importance of a sharing a common problem and a common location in which all participants have an interest. Participatory modelling has proved an effective way to consolidate a diverse body of knowledge and make it accessible. Results demostrate the importance of model outputs that are diagnostic, and which offer insights into the issues under considerations.